Peran Guru Al-Qur’an Hadits dalam Meningkatkan Kemampuan Membaca Al-Qur’an Peserta Didik Kelas VIII C di Mts Ma’arif Kepil Wonosobo - Muhammad Hasan; Nurul Mubin; Ngatoillah Linnaja (Reflection : Islamic Education Journal, 2025)
This Research aims to: 1) determine the ability of students in learning the Qur'an and Hadith at MTs Ma'arif Kepil Wonosobo in reading the Qur'an 2) determine the role of the Qur'an and Hadith teacher in improving the ability to read the Qur'an of Class VIII C students at MTs Ma'arif Kepil Wonosobo 3) determine the implementation of learning the Qur'an and Hadith in improving the ability to read the Qur'an of Class VIII C students at MTs Ma'arif Kepil Wonosobo.This thesis uses descriptive qualitative field research. Data collection techniques use participant observation, in-depth interviews and documentation. The data analysis technique used is by analyzing before the field, then analyzing data in the field using a model to reduce irrelevant data, present data and draw conclusions. The results of this study are: 1) the reading ability of Class VIII C students in learning the Qur'an and Hadith is learning planning, Al-Qur'an and Hadith learning materials, and learning media. 2) The role of Al-Qur'an Hadith teachers in improving the ability to read the Qur'an of Class VIII C students has three scopes, namely opening the lesson by starting with reading Nadhom, delivering the lesson material and closing the lesson. 3) Implementation of Al-Qur'an Hadith learning in improving the ability to read the Qur'an of Class VIII C students. The supporting factors for learning the Qur'an Hadith are the use of appropriate learning media, the reading of the Qur'an after the teacher writes in front. The inhibiting factors for learning the Qur'an Hadith are the students' educational background, student absences, short time, and the emergence of lazy and bored instincts.